Effects of bismuth oxide on the sinterability of hydroxyapatite - Ramesh, Singh; Tan, Chou Yong; Yeo, W. H.; Tolouei, Ranna; Amiriyan, Mahdi; Sopyan, Iis; Teng, Wan Dung (Pergamon, 2011)
The sinterability of Bi2O3-doped hydroxyapatite (HA) has been studied and compared with the undoped HA. Varying amounts of Bi2O3 ranging from 0.05 wt% to 1.0 wt% were mixed with the HA. The study revealed that most sintered samples composed of the HA phase except for compacts containing 0.3, 0.5 and 1.0 wt% Bi2O3 and when sintered above 1100 8C, 1000 8C and 950 8C, respectively. In general, the addition of 0.5 wt% Bi2O3 was identified as the optimum amount to promote densification as well as to improve the mechanical properties of sintered HA at low temperature of 1000 8C. Throughout the sintering regime, the highest value of relative bulk density of 98.7% was obtained for 0.5 wt% Bi2O3-doped HA when sintered at 1000 8C. A maximum Young’s modulus of 119.2 GPa was measured for 0.1 wt% Bi2O3-doped HA when sintered at 1150 8C. Additionally, the ceramic was able to achieve highest hardness of 6.08 GPa and fracture toughness of 1.21 MPa m1/2 at sintering temperature of 1000 8C.